Diagenetic and tectonic evolution of pore networks in carbonate normal fault zones and their effects on permeability - Haines, T.; Michie, E.; Neilson, J.; Healy, D.; Alsop, G.; Timms, Nicholas Eric; Aplin, A. (European Association of Geoscientists and Engineers, EAGE, 2012)
This study quantifies changes in carbonate fabrics and pore network characteristics in fault zones using field analogues with the ultimate aim of understanding fluid flow around carbonate hosted normal fault zones. The shallow water carbonate sequence in Malta, which is dissected by an array of normal faults of varying displacements, is the chosen field analogue. The study reveals a wide range in petrophysical properties on the core plug scale. Porosity ranges from less than 5 % to greater than 35 %, permeability varies by seven orders of magnitude from 0.001 mDs to 1000 mDs and ultrasonic p-wave velocity ranges between 2 and 6 km/s. The range in these petrophysical properties is in part due to primary depositional fabric. However, modifications of the primary fabric during subsequent diagenesis and deformation are important in shaping the petrophysical properties of the rock. Pore throat size and pore type are important characteristics of the pore network which control the permeability. The changes in the carbonate fabrics into fault zones results in pore throat size and pore type changes and hence modifies the permeability. Total porosity and rock fabric are important controls on the p-wave velocity and can allow for predictions of pore network characteristics.